How Biological Activity in Sea Cucumbers Changes as a Function of Species and Tissue - Sabrina Sales; Helena M. Lourenço; Narcisa M. Bandarra; Cláudia Afonso; Joana Matos; Maria João Botelho; Maria Fernanda Pessoa; Pedro M. Félix; Arthur Veronez; Carlos Cardoso (Foods, 2023)
Biological activity and bioactive compound content in sea cucumbers was assessed, considering Parastichopus regalis, Holothuria mammata, Holothuria forskali, and Holothuria arguinensis as species and intestine, muscle band, respiratory tree, body wall, and gonads as tissues. P. regalis had the lowest content in phenolic compounds and antioxidant activity in contrast to Holothuria species. In the respiratory tree, the highest phenolic concentration was recorded in H. arguinensis, 76.4 ± 1.2 mg GAE/100 g dw vs. 21.0–49.0 mg GAE/100 g dw in the other species. H. arguinensis had the highest DPPH and FRAP results in the gonads, 13.6 ± 0.7 mg AAE/100 g dw vs. 2.6–3.5 mg AAE/100 g dw and 27.1 ± 0.3 μmol Fe2+/g dw vs. 8.0–15.9 μmol Fe2+/g dw, respectively. Overall, P. regalis biomass presented the highest anti-inflammatory activity levels and H. arguinensis the lowest anti-inflammatory levels. The respiratory tree was the most anti-inflammatory (measured by the inhibition of cyclooxygenase-2, COX-2) tissue in H. mammata and H. forskali (also the muscle band in this case), 76.3 ± 6.3% and 59.5 ± 3.6% COX-2 inhibition in 1 mg/mL aqueous extracts, respectively. The results demonstrated a variable bioactive potential and advantage in targeting antioxidant properties in the muscle band and anti-inflammatory activity in the respiratory tree, which may constitute a starting point for a biorefinery approach envisaging multiple applications.